2012
DOI: 10.1002/app.37964
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state recycling of polyimide film waste

Abstract: Possibility of the polyimide (PI) films waste recycling by solid-state mechanochemistry was investigated in this study. Obtained PI powder was used for development of thermostable blends and multicomponent tribocompositions, which include additions of carbon black, ultradispersive diamond powder, and quasicrystalls. PI films waste treatment was provided in high-energy planetary ball mill. Powder compositions were mixed by low-energy planetary ball mill. Bulk samples were obtained by compression molding. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Solid-state mecano-chemistry can be successfully applied in the recycling of PI film wastes with the purpose to develop thermostable blends and multicomponent tribocompositions. To gain applicative potential, these can be prepared in combination with other high-performance polymers, carbon black, diamond powder, and Al-Cu-Fe crystals [167].…”
Section: Recycling Of Polyimidesmentioning
confidence: 99%
“…Solid-state mecano-chemistry can be successfully applied in the recycling of PI film wastes with the purpose to develop thermostable blends and multicomponent tribocompositions. To gain applicative potential, these can be prepared in combination with other high-performance polymers, carbon black, diamond powder, and Al-Cu-Fe crystals [167].…”
Section: Recycling Of Polyimidesmentioning
confidence: 99%
“…This indicates that fluoropolymers should be considered as suitable matrices for QC-filled composites. In [ 34 ] FEP-based multicomponent composites were investigated, and it was observed that addition of QC particles significantly increases the wear resistance and decreases the friction coefficient of composites.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in most of composites discussed above icosahedral QC alloys of a Al-Cu-Fe [ 13 , 15 , 17 , 19 , 20 , 21 , 23 , 24 , 29 , 30 , 31 , 32 , 33 , 34 ] system or of Al-Cu-Fe systems alloyed with boron [ 14 , 16 , 26 ] were used as reinforcing particles. Indeed, Al-Cu-Fe is the most investigated QC-forming system, as the icosahedral QC phase in this system is thermodynamically stable, easy to synthesize, and possesses a number of advanced properties [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions is to prepare PI fillers . For example, they could be injection mouldable compositions for tribological applications based on high‐performance thermoplastics, for example, PPS, PEEK, or PBI, with PI powders acting as dispersion fillers with the following benefits over metallic or ceramic fillers: excellent wear resistance, low abrasion, low noise level, self‐lubrication ability. The introduction of recycled powders into thermoplastics is often used in practice to recycle thermoset plastics and rubbers.…”
Section: Introductionmentioning
confidence: 99%